DETERMINAN VOLUNTARY AUDITOR SWITCHING : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Daniel Lianto (Parsimonia - Jurnal Ekonomi dan Bisnis, 2017)
Auditor switching is the replacement of public accounting firms conducted by the company. Auditor switching can occur voluntary or mandatory (compulsory). If voluntary is happening, then the auditor did not continue to cooperate with the company in terms of doing an audit. Voluntary auditor switching can occur from the perspective of auditor and companies. If from the perspective of auditors, the variables that affect are audit fee, audit delay, audit tenure, and others. Whereas if it occurs from the perspective of the client, the variables that affect are financial distress, change management, and others. Auditor Switching Regulations in Indonesia is listed on the Indonesian Minister of Finance Regulation No. 17 / PMK.01 / 2008, which is a reference for a company in replacing its auditor. With the existence of these regulations, companies limited cooperation to the auditors in order to minimize fraud. Moreover, with the presence of these regulations, the firm’s management can get a feedback about which policy can be taken in order of auditor switching and it’s implications for the company. The purpose of this study is to examine the effect of audit delay, going concern audit opinion, auditor reputation, audit fees and audit tenure on auditor voluntary switching. The results of this research indicate that the independent variables that affect the voluntary auditor switching is audit tenure and auditor reputation. While the other independent variables such as audit delay, going concern audit opinion, and audit fee does not affect the voluntary auditor switching.